Preparedness of Quezon City Social Welfare and Development in Conducting Diversion Program in Barangay Kaligayahan Novaliches: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study focused on the Preparedness of Quezon City's Social Welfare and Development inconducting a diversion program in Barangay Kaligayahan Novaliches. Two groups from thebarangay personnel and residents were selected using a purposive sampling technique basedon the result of the Preparedness of Quezon City Social Welfare and Development.The findings suggest that Quezon City Social Welfare and Development is adequatelyprepared to conduct the diversion program in Barangay Kaligayahan. The staff memberspossess the necessary skills, knowledge, and training to implement the program effectively.They also have access to the necessary resources, including facilities and equipment, tosupport the implementation of the program. However, the study also reveals some challengesthat Quezon City Social Welfare and Development may encounter in conducting the program,including the lack of coordination among stakeholders and the limited budget for programimplementation. Furthermore, the study highlights the importance of community involvementand engagement in the successful implementation of the diversion program. The Barangayofficials and youth offenders who participated in the study emphasized the need for morecommunity-based interventions to address the underlying causes of youth delinquency.Overall, the study concludes that Quezon City Social Welfare and Development is adequatelyprepared to conduct the diversion program in Barangay Kaligayahan. However, there is aneed for more collaboration and coordination among stakeholders to ensure the sustainabilityand effectiveness of the program. The study recommends that Quezon City Social Welfareand Development should explore more community-based interventions that involve the activeparticipation of the community, especially the youth and their families. Additionally, there is aneed to secure more funding to support the implementation of the program and ensure its long-term success.
Keywords: Criminology